Doctoral student experiences in biological sciences laboratory rotations. (3rd April 2019) - Maher, Michelle A.; Wofford, Annie M.; Roksa, Josipa; Feldon, David F.
Abstract : Purpose: The purpose of this study is to explore the experience of selecting and engaging in biological sciences laboratory rotations from the perspective of doctoral students. Design/methodology/approach: Within the socialization framework, this study uses a qualitative approach whereby 42 biological sciences students enrolled at highly selective US universities were interviewed in the first and second year of doctoral training about laboratory rotation experiences. Findings: The study revealed how doctoral students used formal and informal information networks, explored research topics, struggled with funding concerns and learned about the social aspect of the laboratories in which they rotated. Originality/value: While rotations are considered a signature pedagogy in the laboratory sciences, students' experiences within them are understudied. This study offers new knowledge about what doctoral students experience while rotating that can be used to inform and improve rotation processes for both students and universities.